Implementing the census-based, impact-oriented approach to comprehensive primary health care over three decades in Montero, Bolivia: 2. Program achievements, including long-term trends in mortality of children and mothers. Issue 1 (2020) - Chavez, Dardo; Claure, Mitma; Moshman, Hilary; Robison, Nathan C; Llanque, Ramiro; Perry, Henry B
No abstract available